Emotion understanding and the moral self-concept as motivators of prosocial behavior in middle childhood - Christner, Natalie; Pletti, Carolina; Paulus, Markus (Cognitive development, 2020)
•Theories propose that the moral self-concept and positive emotions promote prosocial behavior.•Changes in both consequential and anticipated emotions explained age differences of sharing.•Reflecting on the affective consequences of (not-)sharing increased subsequent sharing behavior.•Anticipation of negative emotions tended to mediate a relation between self-concept and behavior. The moral self-concept reflects the view of oneself in terms of moral behavior and has been proposed to predict actual behavior. Theories also suggest emotions and emotion knowledge to predict prosocial behavior, but the interplay between the moral self-concept and emotions is largely unknown. This interplay is especially important to study in middle childhood, a relevant period for the ontogeny of the moral self-concept and when emotions regarding prosocial behavior are suggested to change. The current study explored the nature of the relation between the moral self-concept, prosocial behavior, and consequential emotions (Experiment 1) or anticipated emotions (Experiment 2) regarding prosocial behavior in 5- to 9-year-olds (together N = 169). Moreover, we investigated whether emotions mediate the relation between the moral self-concept and prosocial behavior. Overall, the moral self-concept was positively related to prosocial behavior. In addition, emotional consequences as well as anticipated emotions explained age differences in sharing behavior. Moreover, the results hint to an indirect effect of the moral self-concept on sharing behavior through the anticipation of negative feelings when not-sharing. Interestingly, children who first reflected about the affective consequences of prosocial behavior seemed to share more. In line with theories, the results demonstrate that both the moral self-concept and emotions are relevant motivators of prosocial behavior in middle childhood.